Automated tube voltage adaptation in head and neck computed tomography between 120 and 100 kV: effects on image quality and radiation dose - May, Matthias; Kramer, Manuel; Eller, Achim; Wüst, Wolfgang; Scharf, Michael; Brand, Michael; Saake, Marc; Schmidt, Bernhard; Uder, Michael; Lell, Michael (Neuroradiology, 2014)
Low tube voltage allows for computed tomography (CT) imaging with increased iodine contrast at reduced radiation dose. We sought to evaluate the image quality and potential dose reduction using a combination of attenuation based tube current modulation (TCM) and automated tube voltage adaptation (TVA) between 100 and 120 kV in CT of the head and neck.One hundred thirty consecutive patients with indication for head and neck CT were examined with a 128-slice system capable of TCM and TVA. Reference protocol was set at 120 kV. Tube voltage was reduced to 100 kV whenever proposed by automated analysis of the localizer. An additional small scan aligned to the jaw was performed at a fixed 120 kV setting. Image quality was assessed by two radiologists on a standardized Likert-scale and measurements of signal- (SNR) and contrast-to-noise ratio (CNR). Radiation dose was assessed as CTDIvol.Diagnostic image quality was excellent in both groups and did not differ significantly (p = 0.34). Image noise in the 100 kV data was increased and SNR decreased (17.8/9.6) in the jugular veins and the sternocleidomastoid muscle when compared to 120 kV (SNR 24.4/10.3), but not in fatty tissue and air. However, CNR did not differ statistically significant between 100 (23.5/14.4/9.4) and 120 kV data (24.2/15.3/8.6) while radiation dose was decreased by 7-8%.TVA between 100 and 120 kV in combination with TCM led to a radiation dose reduction compared to TCM alone, while keeping CNR constant though maintaining diagnostic image quality.
EVALuna2:14375